FREQUENCY OF DEPRESSION AND ANXIETY IN PATIENTS ATTENDING A DIABETES CLINIC - Azad, Nadia; Gondal, Murtaza; Abbas, Nadeem; Shahid, Afshan (Journal of Ayub Medical College Abbottabad, 2014)
Background: Depression is very common among people with type-2 diabetes and is associated with poor treatment compliance and outcome. This study was done to see the frequency of depression in patients with established type-2 diabetes attending a diabetes clinic in a tertiary care hospital. Methods: One hundred and ten patients with chronic type-2 diabetes were included in this cross sectional study, excluding type-1 diabetics, patients with severe co-morbid illness with type-2 diabetes and patients with some psychiatric illness. Hospital Anxiety and Depression Scale was used to assess depression and anxiety in these patients. Results: Almost 50% of patients were found to have anxiety and depression in our study. Female gender, lack of education and housewives were found to be effected more while duration of diabetes, treatment and control of diabetes have little effect on anxiety and depression in patients with chronic type-2 diabetes patients. Conclusion: There is a high incidence of depression and anxiety in patients with chronic type-2 diabetes and clinicians must screen regularly for better care of these patients. Keywords: Depression, anxiety, type-2 diabetes mellitus, diabetes clinic